1987
DOI: 10.1103/physrevb.36.4531
|View full text |Cite
|
Sign up to set email alerts
|

Photocapacitance study of pressure-induced deep donors in GaAs: Si

Abstract: concluded that these pressure induced deep donors (to be abbreviated as PIDD in this article) in GaAs are identical to the DX centers in GaAlAs.To substantiate this conclusion it is necessary to compare all the known properties of the DX centers with that of the PIDD in GaAs.The hydraulic press at room temperature. The pressure was determined by the standard ruhy fluorescence technique. 5Two optical measurements have been performed to study the properties of the PIDD in GaAs. In the first experiment the depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The decay of the photocurrent according the power law has been observed in many inhomogeneous binary and ternary semiconductors and in modulation doped amorphous silicon [1,3,13,21,22]. It has also been shown that in some ternary II-VI and III-V solid solutions at low temperatures the relaxation of PPC shows a stretched-exponential behavior but the link between those two types of decay has not been established yet [8].…”
Section: Resultsmentioning
confidence: 94%
“…The decay of the photocurrent according the power law has been observed in many inhomogeneous binary and ternary semiconductors and in modulation doped amorphous silicon [1,3,13,21,22]. It has also been shown that in some ternary II-VI and III-V solid solutions at low temperatures the relaxation of PPC shows a stretched-exponential behavior but the link between those two types of decay has not been established yet [8].…”
Section: Resultsmentioning
confidence: 94%
“…With only minor modifications, this technique has also been used for various dc-and ac-impedance studies [30,31]. Experiments in the DACs have been carried out over an ultrawide range of hydrostatic pressures reaching $500 GPa [32,33]. Sapphire-anvil cell (SAC), a parent and considerably cheaper modality of DAC, has been used at lower pressures (up to $10 GPa) [34].…”
Section: Introductionmentioning
confidence: 99%
“…The large capture barrier of trap A is similar to the DX centre (Lang 1986, Mooney 1990, Malloy and Khachaturyan 1993, Li and Yu 1993. It is already clear that DX centre is introduced by a simple substitutional donor (Mizuta et al 1985, Li et al 1987, Chadi and Chang, 1988, 1989, Mooney 1990, Malloy and Khachaturyan 1993, Li and Yu 1993, not a complex of donor impurity and other unknown defect, as suggested by Lang (1986) in early days. The trap A concentration is two orders of magnitude lower than the Te doping concentration.…”
Section: Electron Trap Amentioning
confidence: 87%